2022
DOI: 10.25077/jka.v11i1.1984
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Tingkat Kecukupan Vitamin A, Zat Besi, dan Zink pada Balita Stunting dan Non Stunting di Kabupaten Banyuasin

Abstract: Stunting is a chronic nutritional problem in toddlers of a shorter height than children his age. The impact of stunting is not only in terms of health but also affects the level of intelligence of children. Toddlers who lack vitamin A, iron, and zinc can cause cognitive and physical impairment and an increased risk of death. Objectives: To determined the difference in the level of adequacy of vitamin A, the level of adequacy of iron and the level of adequacy of zinc in stunting and non-stunted toddlers. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
4
0
3
Order By: Relevance
“…The results of this study analysis showed that the most common indicators of Behavior of Nutrition-aware Families were still lack of nutritional supplements, namely Fe tablets and vitamin A (71.1%), regular weight weighing (67.2%), and exclusive breastfeeding for up to 6 months (56.5%). This study is in line with previous research that the incidence of stunting correlates with exclusive breastfeeding for up to 6 months (Lindawati et al, 2023;Hadi et al, 2022), visits to integrated health posts with child weighing (Prasetyani et al, 2023), and supplementation of Fe and vitamin A (Silaban et al, 2022).…”
Section: Behavior Of Nutrition-aware Families and The Incidence Of St...supporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study analysis showed that the most common indicators of Behavior of Nutrition-aware Families were still lack of nutritional supplements, namely Fe tablets and vitamin A (71.1%), regular weight weighing (67.2%), and exclusive breastfeeding for up to 6 months (56.5%). This study is in line with previous research that the incidence of stunting correlates with exclusive breastfeeding for up to 6 months (Lindawati et al, 2023;Hadi et al, 2022), visits to integrated health posts with child weighing (Prasetyani et al, 2023), and supplementation of Fe and vitamin A (Silaban et al, 2022).…”
Section: Behavior Of Nutrition-aware Families and The Incidence Of St...supporting
confidence: 92%
“…Five indicators of Nutrition-aware behavior from the results of the study have been shown to contribute to the incidence of stunting in children (Lindawati et al, 2023;Rosalina et al, 2023;Berawi et al, 2022;Nahak et al, 2022;Fitriah et al, 2021). Another study shows that there is a contribution to Nutrition-aware family indicators, namely weight weighing in Posyandu (Prasetyani et al, 2023), exclusive breastfeeding (Lindawati et al, 2023;Hadi et al, 2022), feeding practices (Quamme &;Iversen, 20220;Gunawan et al, 2022), iodized salt consumption (Abbag et al, 2021;Gunawan et al, 2022), Fe and vitamin A supplements (Silaban et al, 2022), against the incidence of stunting in children. However, research obtained different results that breastfeeding until the first 6 months did not correlate with the incidence of stunting, even further multivariate analysis showed exclusive breastfeeding was protective in mothers ≥ 30 years (Hikmahrachim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Stunted children have lower hemoglobin concentrations than non-stunted children. Iron deficiency anemia can be prevented by consuming foods high in iron, especially from animal sources [11]. Pumpkin tuna nuggets, broccoli tuna nuggets, and red bean tuna nuggets are made to meet the needs of vitamin A, zinc, and iron.…”
Section: Discussionmentioning
confidence: 99%
“…Kemudian penelian lain jg mengatakan Ada hubungan yang signifikan antara asupan seng (p=0.000), asupan zat besi (p=0.007) dan kejadian stunting. (Silaban et al, 2022).…”
Section: Latar Belakang Pengabdianunclassified